2020
DOI: 10.3389/fendo.2020.568500
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Changes in Circulating Endocrine FGF19 Subfamily and Fetuin-A in Response to Intralipid and Insulin Infusions in Healthy and PCOS Women

Abstract: Background: The fibroblast growth factors (FGF) 19 subfamily, also referred to as endocrine FGFs, includes FGF19, FGF21, and FGF23 are metabolic hormones involved in the regulation of glucose and lipid metabolism. Fetuin-A is a hepatokine involved in the regulation of beta-cell function and insulin resistance. Endocrine FGFs and fetuin-A are dysregulated in metabolic disorders including obesity, type 2 diabetes, non-alcoholic fatty liver disease and polycystic ovary syndrome (PCOS). Our study was designed to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 51 publications
0
12
1
Order By: Relevance
“…During each exercise session, heart rate and inspired/expired gas fractions were continuously monitored and heart rate equivalent to 60% of baseline VO 2max was achieved during each session of exercise training ( 27 ). Insulin sensitivity was measured using the gold standard euglycemic clamp technique as described previously ( 28 , 29 ). Within a week following the completion of exercise protocol, all participants were invited to provide blood samples and underwent insulin sensitivity test.…”
Section: Methodsmentioning
confidence: 99%
“…During each exercise session, heart rate and inspired/expired gas fractions were continuously monitored and heart rate equivalent to 60% of baseline VO 2max was achieved during each session of exercise training ( 27 ). Insulin sensitivity was measured using the gold standard euglycemic clamp technique as described previously ( 28 , 29 ). Within a week following the completion of exercise protocol, all participants were invited to provide blood samples and underwent insulin sensitivity test.…”
Section: Methodsmentioning
confidence: 99%
“… 28 , 33 , 34 FGF-19 levels have been published as decreased or unchanged in patients with PCOS. 27 As our recruitment population was from an underserved rural area with high levels of diabetes and obesity, it is possible that distribution patterns of bile acids are affected heterogeneously depending on environmental queues.…”
Section: Discussionmentioning
confidence: 99%
“…FGF-21 plays a key role in the metabolic process as a hepatic, adipokine and myokine. It appears to function through FGFR1c-mediated binding to β-klotho to form complexes ( 21 ). Circulating FGF21 is primarily expressed by the liver when the body is starving, obese, mitochondrial dysfunction and aging, while FGF21 expression is barely detectable in healthy conditions ( 22 ).…”
Section: The Endocrine Subfamily Of Fgfsmentioning
confidence: 99%
“…FGF-21 is mainly expressed by the liver and acts as a potent activator of glucose uptake by inducing glucose transporter 1 (GLUT1) on adipocytes, which reverses hepatic steatosis and improves insulin sensitivity in obese mice ( 67 ). A study on the effect of insulin on endocrine FGFs in women with PCOS found that insulin administration increased plasma levels of FGF-21 in healthy controls and women with PCOS, suppressed plasma levels of FGF-19 in healthy controls, and had no effect on plasma levels of FGF-23 ( 21 ). An earlier study evaluated FGF-21 levels in PCOS and found that circulating FGF-21 levels were higher in PCOS patients and correlated with homeostasis model assessment insulin resistance index (HOMA-IR) ( 68 ).…”
Section: Fgf19 Subfamily In Polycystic Ovary Syndrome (Pcos)mentioning
confidence: 99%